2021
DOI: 10.1038/s41433-021-01815-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of posterior capsule–intraocular lens interaction with and without primary posterior capsulorrhexis: an intraindividual randomized trial

Abstract: Purpose To assess the morphologic and clinical features of posterior capsule-intraocular lens (IOL) interaction following cataract surgery with and without primary posterior continuous curvilinear capsulorrhexis (PPCCC) at a three-dimensional (3-D) level using Scheimpflug imaging. Methods This prospective intraindividual randomized comparative study comprised 56 patients (112 eyes) with age-related cataract who had bilateral cataract surgery and hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…[23][24][25] Given our previous results that observed an earlier and firmer adhesion between the IOL optic and the posterior capsule in PPCCC eyes, we conjecture that PPCCC may lead to better IOL stability resulting from the earlier and firm capsule-IOL complex formation. 13 Similarly, Kim et al pointed out that IOL displacement attributable to capsular contraction was B: Comparison of the mean internal tilt between the PPCCC group and the NPCCC group at 1 day, 1 week, 1 month, and 3 months. NPCCC = no posterior continuous curvilinear capsulorhexis; PPCCC = primary posterior continuous curvilinear capsulorhexis reduced when cataract surgery involved PPCCC; however, in contrast with our results, no significant between-group difference in IOL decentration was found.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…[23][24][25] Given our previous results that observed an earlier and firmer adhesion between the IOL optic and the posterior capsule in PPCCC eyes, we conjecture that PPCCC may lead to better IOL stability resulting from the earlier and firm capsule-IOL complex formation. 13 Similarly, Kim et al pointed out that IOL displacement attributable to capsular contraction was B: Comparison of the mean internal tilt between the PPCCC group and the NPCCC group at 1 day, 1 week, 1 month, and 3 months. NPCCC = no posterior continuous curvilinear capsulorhexis; PPCCC = primary posterior continuous curvilinear capsulorhexis reduced when cataract surgery involved PPCCC; however, in contrast with our results, no significant between-group difference in IOL decentration was found.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 In our previous study, we found earlier optic-posterior capsular adhesion and good axial stability in eyes with PPCCC. 13 Therefore, we proposed that PPCCC might provide better IOL centration to lessen aberrations and improve visual quality. In this prospective intraindividual study, we evaluated IOL tilt and decentration and their effects on HOAs after cataract surgery with and without PPCCC based on a 1-piece 360-degree square-edge acrylic IOL, which might become the most popular design mode of the premium IOL in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 6 Yu et al, using Scheimpflug imaging, also observed faster postoperative posterior capsule adhesion to the IOL and stabilization in eyes with PPCCC than in the control group, without PPCCC. 7 …”
Section: Introductionmentioning
confidence: 99%